Die ontmaskering van die bose: Eksegetiese perspektiewe op geweld in Openbaring 18 - De Villiers, Pieter G. R. (HTS teologiese studies, 2008)
Exposure of evil: Exegetical perspectives on violence in Revelation 18 This article investigates violence in Revelation 18 from an exegetical perspective because of its prominent role in contemporary debate on violence in the New Testament. It first discusses the complex meaning of violence in the light of the intricate composition of the book as a whole and this chapter in particular. It argues that, in contrast to what is often said in contemporary research about the incoherence of this passage, Revelation 18 is in fact a carefully composed ring composition in which the constitutive elements determine its meaning decisively and in which violence is a seminal motif. It also discusses how the rest of the text confirms the author’s literary skills and the neat composition of Revelation 18 as a text about a violent city. The article then shows how the different elements in the text ironically delineate the downfall of the violent city of Babylon and the reasons for it. It sketches how the consequences of Babylon’s fall are developed from an earthly and divine perspective. In all these different parts the prevalence of violence is spelled out.